Application of Cone Beam Computed Tomography in Endodontics: A Review Article - Narjes Hoshyari; Kumars Nazari Moghaddam (Islamic Dental Association of Iran, 2014)
Background and Aim : Cone beam computed tomography (CBCT) has attracted considerable attention as a new diagnostic imaging technique in dentistry. The aim of this study was to review its application in Endodontics .   Materials and Methods : Electronic databases (MedLine, EMBase, Cochrane, Iran Medex, Science citation index, Scopus and Google scholar) were searched by the authors for articles published from 1999 to 2012. "CBCT imaging", "Endodontics", "vertical root fracture or VRF" and "periapical or PA lesions" were the searched key words .   Results : The assessment of PA lesions, healing process, tooth morphology, accessory canals, root curvature, traumatic injuries, internal and external tooth surfaces, root resorption, fracture lines specially vertical root fracture, perforations, broken instruments, over-extended filling materials, calcified canals, proximity and superimposition of roots and pre-surgical evaluation are the challenges that cannot be adequately addressed by conventional radiography.   Conclusion : Cone beam computed tomography is a valuable imaging modality with minimal radiation exposure to the patient that provides maximal information for the clinician. It is going to be the front-line dental imaging modality in near future .